(untitled) (International Journal of Innovative Technologies in Economy, 2021)
Modern fulfillment of foreign debt obligations and successful foreign trade policy should become decisive factors in raising Ukraine’s rating to the investment level and developing interest in our country as an object of investment of foreign and domestic investors.